XBP1s Is an Anti-lipogenic Protein - Herrema, Hilde (J Biol Chem, 2016)
Endoplasmic reticulum (ER) stress has been shown to contribute to various metabolic diseases, including non-alcoholic fatty liver disease and type 2 diabetes. Reduction of ER stress by treatment with chemical chaperones or overexpression of ER chaperone proteins alleviates hepatic steatosis. Nonetheless, X-box binding protein 1s (XBP1s), a key transcription factor that reduces ER stress, has been proposed as a lipogenic transcription factor. In this report, we document that XBP1s leads to suppression of lipogenic gene expression and reduction of hepatic triglyceride and diacylglycerol content in livers of diet-induced obese and genetically obese and insulin-resistant ob/ob mice. Furthermore, we also show that PKCϵ activity, which correlates with fatty liver and which causes insulin resistance, was significantly reduced in diet-induced obese mice. Finally, we have shown that XBP1s reduces the hepatic fatty acid synthesis rate and enhances macrolipophagy, an initiating step in lipolysis. Our results reveal that XBP1s reduces hepatic lipogenic gene expression and improves hepatosteatosis in mouse models of obesity and insulin resistance, which leads us to conclude that XBP1s has anti-lipogenic properties in the liver.